Effect of wear debris of Al2O3, ZrO2 and WC balls on Y-α/β-SiAlON ceramics consolidated by spark plasma sintering - Chun, Sungsu; Min, Bong-Ki; Han, Young-Hwan; Kim, Young-Moon; Lee, Kyeongseok; Jung, Young Geun; Kim, Kwang-Ho; Kim, Young-Ki; Kim, Sukyoung (Metals and materials international, 2013)
Three types of Y-α/β-SiAlON powders were prepared by mixing and milling the raw materials for 20 h using Al 2 O 3 , ZrO 2 , and WC balls, thereafter denoted as SNA, SNZ and SNW, respectively. The three types of specimens were sintered using spark plasma sintering (SPS) at 1510 °C for 5 min under 30 MPa in a vacuum. α-phases (SiAlON and Si 3 N 4 ) and β-SiAlON phase were observed in the SNA and SNZ specimens, but only the β-SiAlON phase existed in the SNW specimen. The wear debris of the WC balls affected the grain boundary properties and eventually promoted the full phase transformation of α-Si 3 N 4 into α- and β-SiAlON phases. However, SNA and SNZ were partially transformed into α- and β-SiAlON phases. The Vickers hardness of SNA was the highest (18.7 GPa), due to its having the highest content of α-phase, but its fracture toughness was the lowest (4.09 MPam 1/2 ) due to its having the lowest content of β-SiAlON phase. The wear debris and secondary phases existed at the grain boundary, mostly at the triple junction, and also affected the color. The color of the sintered specimen was quite different depending on the milling media.